Development of Educational Game "Jagocah" using Scratch on Fraction Material in 4 Grade Primary School - Jasmine, Anastasya Trisha; Nurain, Ni Luh Sakinah; Putra, Arda Purnama (Proceedings Series of Educational Studies, 2024)
The lesson of unit fraction and common denominator fraction on grade 4 of elemetary school is stilldificult to understand by the students. According to the observation done in SDN 3 SumbersariMalang, only 30% of the students could grasp the concept of unit fraction and commondenominator fraction proficiently. The lack of understanding of the lesson could be contributed tothe lack of learning media that could be use practically during the learning process. The objective ofthis research is to create a web-based educational game as a learning medium for students and toevaluate its validity and practicality. The research findings educational game that has been validatedand tested with the validity score of 96% by the content expert, 80% by the media expert and 91%valid by the teacher as well as the practicality percentage of 94% from the data obtain by thestudents as the user of the media. Keywords: keyword 1; keyword 2; keyword 3